BONE MARROW MICROENVIRONMENT INVOLVEMENT IN T-MN: FOCUS ON MESENCHYMAL STEM CELLS - Maria Teresa Voso; Giulia Falconi; Emiliano Fabiani (Mediterranean Journal of Hematology and Infectious Diseases)
Therapy-related myeloid neoplasms (t-MN) are a late complication of cytotoxic therapy (CT) used in the treatment of both malignant and non-malignant diseases. Historically, t-MN has been considered to be a direct consequence of DNA damage induced in normal hematopoietic stem or progenitor cells (HSPC) by CT. However, we now know that treatment-induced mutations in HSC are not the only players involved in t-MN development but additional factors may contribute to the onset of t-MN.